in Local Regulation Patterns Towards Competitive Coastal Tourism in West Coastal Village - Yuswanto Yuswanto; Marlia Eka Putri; Ade Arif Firmansyah (Fakultas Hukum Universitas Hang Tuah, 2020)
This study aims to create an ideal pattern of local regulation to create competitive coastal tourism in West Coastal Village. By using doctrinal/normative research methods which mainly analyze secondary data consisting of: primary legal materials, secondary legal materials and tertiary legal materials, the regional regulation patterns will be constructed which are ideal for realizing competitive coastal tourism in West Coastal Village. The stages of the research to be carried out are divided into three parts as follows: first, identifying and inventorying the laws and regulations relating to the implementation of tourism; secondly, evaluating and drafting an academic manuscript regarding the implementation of tourism; thirdly compose the ideal regional regulation pattern to realize competitive coastal tourism in the West Coast Regency. The results showed that the ideal local regulation pattern for realizing competitive coastal tourism in West Coastal Village contained the following minimum content material: namely: general provisions; principles and objectives; policies and strategies; establishment of a competitive beach tourism area; development of competitive coastal tourism areas; implementation and control; closing.